STR DNA genotyping of hydatidiform moles in South China - Zheng, Xing-Zheng (e-Century Publishing Corporation, 2014)
Objective: To evacuate whether short-tandem-repeat (STR) DNA genotyping is effective for diagnostic measure to precisely classify hydatidiform moles. Methods: 150 cases were selected based on histologic features that were previously diagnosed or suspected molar pregnancy. All sections were stained with hematoxylin as a quality control method, and guided the microscopic dissection. DNA was extracted from dissected chorionic villi and paired maternal endometrial FFPE tissue sections. Then, STR DNA genotyping was performed by AmpFlSTR(®) Sinofiler(TM) PCR Amplification system (Applied Biosystems, Inc). Data collection and analysis were carried out using GeneMapper(®) ID-X version 1.2 (Applied Biosystems, Inc). Results: DNA genotyping was informative in all cases, leading to identification of 129 cases with abnormal genotype, including 95 complete and 34 partial moles, except 4 cases failed in PCR. Among 95 complete moles, 92 cases were monospermic and three were dispermic. Among 34 partial moles, 32 were dispermic and 2 were monospermic. The remaining 17 cases were balanced biallelic gestations. Conclusion: STR DNA genotyping is effective for diagnostic measure to precisely classify hydatidiform moles. And in the absence of laser capture microdissection (LCM), hematoxylin staining plus manual dissection under microscopic guided is a more economic and practical method.